Question
upstudy study bank question image url

nd the value of the ratios below in terms of \( \sqrt{2} \) and \( \sqrt{3} \) using the sum or fference of two special angles. Simplify your answers. \( \begin{array}{llll}\cos 15^{\circ} \\ \left.\text { [Hint: } 15^{\circ}=60^{\circ}-45^{\circ}\right] & 4.2 & \sin 75^{\circ} \\ 3 \cos 105^{\circ} & 4.4 & \sin 195^{\circ} \\ 5 & \sin 165^{\circ} & 4.6 & \tan 15^{\circ}\end{array} \)

Ask by Hammond Romero. in South Africa
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ \tan 15^{\circ} = \frac{\sqrt{3} - 1}{1 + \sqrt{3}} \]

Solution

To find the values of the trigonometric functions in terms of \( \sqrt{2} \) and \( \sqrt{3} \), we will use the sum or difference of angles where applicable. Let's solve each part step by step. ### 1. \( \cos 15^{\circ} \) Using the hint \( 15^{\circ} = 60^{\circ} - 45^{\circ} \), we apply the cosine difference formula: \[ \cos(a - b) = \cos a \cos b + \sin a \sin b \] where \( a = 60^{\circ} \) and \( b = 45^{\circ} \). Calculating: - \( \cos 60^{\circ} = \frac{1}{2} \) - \( \sin 60^{\circ} = \frac{\sqrt{3}}{2} \) - \( \cos 45^{\circ} = \frac{\sqrt{2}}{2} \) - \( \sin 45^{\circ} = \frac{\sqrt{2}}{2} \) Now substituting into the formula: \[ \cos 15^{\circ} = \cos 60^{\circ} \cos 45^{\circ} + \sin 60^{\circ} \sin 45^{\circ} \] \[ = \left(\frac{1}{2} \cdot \frac{\sqrt{2}}{2}\right) + \left(\frac{\sqrt{3}}{2} \cdot \frac{\sqrt{2}}{2}\right) \] \[ = \frac{\sqrt{2}}{4} + \frac{\sqrt{6}}{4} = \frac{\sqrt{2} + \sqrt{6}}{4} \] ### 2. \( \sin 75^{\circ} \) Using the identity \( 75^{\circ} = 45^{\circ} + 30^{\circ} \): \[ \sin(a + b) = \sin a \cos b + \cos a \sin b \] where \( a = 45^{\circ} \) and \( b = 30^{\circ} \). Calculating: - \( \sin 45^{\circ} = \frac{\sqrt{2}}{2} \) - \( \cos 45^{\circ} = \frac{\sqrt{2}}{2} \) - \( \sin 30^{\circ} = \frac{1}{2} \) - \( \cos 30^{\circ} = \frac{\sqrt{3}}{2} \) Now substituting into the formula: \[ \sin 75^{\circ} = \sin 45^{\circ} \cos 30^{\circ} + \cos 45^{\circ} \sin 30^{\circ} \] \[ = \left(\frac{\sqrt{2}}{2} \cdot \frac{\sqrt{3}}{2}\right) + \left(\frac{\sqrt{2}}{2} \cdot \frac{1}{2}\right) \] \[ = \frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} = \frac{\sqrt{6} + \sqrt{2}}{4} \] ### 3. \( \cos 105^{\circ} \) Using \( 105^{\circ} = 180^{\circ} - 75^{\circ} \): \[ \cos(180^{\circ} - x) = -\cos x \] Thus, \[ \cos 105^{\circ} = -\cos 75^{\circ} \] From the previous calculation, we have: \[ \cos 75^{\circ} = \frac{\sqrt{6} - \sqrt{2}}{4} \] So, \[ \cos 105^{\circ} = -\frac{\sqrt{6} - \sqrt{2}}{4} = \frac{\sqrt{2} - \sqrt{6}}{4} \] ### 4. \( \sin 195^{\circ} \) Using \( 195^{\circ} = 180^{\circ} + 15^{\circ} \): \[ \sin(180^{\circ} + x) = -\sin x \] Thus, \[ \sin 195^{\circ} = -\sin 15^{\circ} \] Using the sine difference formula for \( \sin 15^{\circ} \): \[ \sin 15^{\circ} = \sin(60^{\circ} - 45^{\circ}) = \sin 60^{\circ} \cos 45^{\circ} - \cos 60^{\circ} \sin 45^{\circ} \] \[ = \left(\frac{\sqrt{3}}{2} \cdot \frac{\sqrt{2}}{2}\right) - \left(\frac{1}{2} \cdot \frac{\sqrt{2}}{2}\right) \] \[ = \frac{\sqrt{6}}{4} - \frac{\sqrt{2}}{4} = \frac{\sqrt{6} - \sqrt{2}}{4} \] Thus, \[ \sin 195^{\circ} = -\frac{\sqrt{6} - \sqrt{2}}{4} = \frac{\sqrt{2} - \sqrt{6}}{4} \] ### 5. \( \sin 165^{\circ} \) Using \( 165^{\circ} = 180^{\circ} - 15^{\circ} \): \[ \sin(180^{\circ} - x) = \sin x \] Thus, \[ \sin 165^{\circ} = \sin 15^{\circ} = \frac{\sqrt{6} - \sqrt{2}}{4} \] ### 6. \( \tan 15^{\circ} \) Using the identity \( \tan(a - b) = \frac{\tan a - \tan b}{1 + \tan a \tan b} \): \[ \tan 15^{\circ} = \tan(60^{\circ} - 45^{\circ}) = \frac{\tan 60^{\circ} - \tan 45^{\circ}}{1 + \tan 60^{\circ} \tan 45^{\circ}} \] Calculating: - \( \tan 60^{\circ} = \sqrt{3} \) - \( \tan 45^{\circ} = 1 \) Substituting: \[ \tan 15^{\circ} = \frac{\sqrt{3} - 1}{1 + \sqrt{3} \cdot 1} = \

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find the values of the trigonometric functions listed, let's simplify them using angle sum or difference identities: For \( \cos 15^{\circ} = \cos(60^{\circ} - 45^{\circ}) \): Using the cosine difference identity, we have: \[ \cos(60^{\circ})\cos(45^{\circ}) + \sin(60^{\circ})\sin(45^{\circ}) = \frac{1}{2} \cdot \frac{\sqrt{2}}{2} + \frac{\sqrt{3}}{2} \cdot \frac{\sqrt{2}}{2} = \frac{\sqrt{2}}{4} + \frac{\sqrt{6}}{4} = \frac{\sqrt{2} + \sqrt{6}}{4} \] Now for \( \sin 75^{\circ} = \sin(45^{\circ} + 30^{\circ}) \): Using the sine sum identity, we have: \[ \sin(45^{\circ})\cos(30^{\circ}) + \cos(45^{\circ})\sin(30^{\circ}) = \frac{\sqrt{2}}{2} \cdot \frac{\sqrt{3}}{2} + \frac{\sqrt{2}}{2} \cdot \frac{1}{2} = \frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} = \frac{\sqrt{6} + \sqrt{2}}{4} \] Next, for \( \cos 105^{\circ} = \cos(60^{\circ} + 45^{\circ}) \): Using the cosine sum identity: \[ -\left(\cos(60^{\circ})\cos(45^{\circ}) - \sin(60^{\circ})\sin(45^{\circ})\right) = -\left( \frac{1}{2} \cdot \frac{\sqrt{2}}{2} - \frac{\sqrt{3}}{2} \cdot \frac{\sqrt{2}}{2} \right) = -\left(\frac{\sqrt{2}}{4} - \frac{\sqrt{6}}{4}\right) = \frac{\sqrt{6} - \sqrt{2}}{4} \] For \( \sin 195^{\circ} = \sin(180^{\circ} + 15^{\circ}) \): Here, we know that: \[ \sin(195^{\circ}) = -\sin(15^{\circ}) = -\left(\sin(60^{\circ} - 45^{\circ})\right) = -\left(\sin(60^{\circ}) \cos(45^{\circ}) - \cos(60^{\circ}) \sin(45^{\circ})\right) \] This gives: \[ -\left(\frac{\sqrt{3}}{2} \cdot \frac{\sqrt{2}}{2} - \frac{1}{2} \cdot \frac{\sqrt{2}}{2}\right) = -\left(\frac{\sqrt{6}}{4} - \frac{\sqrt{2}}{4}\right) = -\frac{\sqrt{6} - \sqrt{2}}{4} \] For \( \sin 165^{\circ} = \sin(180^{\circ} - 15^{\circ}) \): Thus: \[ \sin(165^{\circ}) = \sin(15^{\circ}) = \frac{\sqrt{6} - \sqrt{2}}{4} \] Lastly, for \( \tan 15^{\circ} \): \[ \tan(15^{\circ}) = \frac{\tan(60^{\circ} - 45^{\circ})}{1 + \tan(60^{\circ})\tan(45^{\circ})} = \frac{\frac{\sqrt{3} - 1}{\sqrt{3} + 1}}{1 + \sqrt{3}} = \frac{(\sqrt{3} - 1)(\sqrt{3} - 1)}{2} = \frac{4 - 2\sqrt{3}}{2} = 2 - \sqrt{3} \] Summarizing the values: - \( \cos 15^{\circ} = \frac{\sqrt{2} + \sqrt{6}}{4} \) - \( \sin 75^{\circ} = \frac{\sqrt{6} + \sqrt

Related Questions

8. Simplify without using a calculator. (8.1) \( \frac{\sin \left(180^{\circ}-x\right) \cdot \tan \left(360^{\circ}-x\right)}{\cos \left(80^{\circ}-x\right)} \times \frac{\cos \left(-180^{\circ}-x\right)}{\cos \left(360^{\circ}+x\right) \sin \left(360^{\circ}-x\right)} \) \( 8.2 \frac{\cos 135^{\circ} \sin 160^{\circ}}{\sin 225^{\circ} \cos 70^{\circ}} \) (8.3) \( \frac{\sin (-\theta)+\cos 120^{\circ}+\tan \left(-180^{\circ}-\theta\right)}{\sin ^{2} 225^{\circ}-\tan (-\theta)-\cos \left(90^{\circ}+\theta\right)} \) B.4 \( 4^{x} \frac{\sin 247^{\circ} \cdot \tan 23^{\circ} \cdot \cos 113^{\circ}}{\sin \left(-157^{\circ}\right)} \) (8.5) \( \frac{3 \cos 150^{\circ} \cdot \sin 270^{\circ}}{\tan \left(-45^{\circ}\right) \cdot \cos 600^{\circ}} \) 8.6) \( \frac{\tan \left(180^{\circ}-x\right) \cdot \sin \left(90^{\circ}+x\right)}{\sin (-x)}-\sin y \cdot \cos \left(90^{\circ}-y\right) \) \( 8.7 \frac{\tan 30^{\circ} \cdot \sin 60^{\circ} \cdot \cos 25^{\circ}}{\cos 135^{\circ} \cdot \sin \left(-45^{\circ}\right) \cdot \sin 65^{\circ}} \) 6.8) \( \frac{\tan \left(180^{\circ}-x\right) \cdot \sin \left(90^{\circ}-x\right)}{\cos \left(90^{\circ}+x\right)}-\frac{\cos \left(180^{\circ}-x\right)}{\sin \left(90^{\circ}+x\right)} \) \( 8.9 \frac{\sin 189^{\circ}}{\tan 549^{\circ}}-\frac{\cos ^{2}\left(-9^{\circ}\right)}{\sin 99^{\circ}} \) Solving trigonometric equations (no calculators) (1.) If \( \sin \mathrm{A}=\frac{-3}{5} \) and \( 0^{\circ}<\mathrm{A}<270^{\circ} \) determine the value of: \( 1.1 \cos A \) \( 1.2 \tan A \). (2.) If \( -5 \tan \theta-3=0 \) and \( \sin \theta<0 \), determine: \( 2.1 \sin ^{2} \theta^{\circ} \) \( 2.25 \cos \theta \) \( 2.3 \quad 1-\cos ^{2} \theta \) 3. If \( 13 \cos \theta+12=0 \) and \( 180^{\circ}<\theta<360^{\circ} \), evaluate: \( 3.2 \tan \theta \) \( 3.1 \sin \theta \cos \theta \) \( 3.3 \sin ^{2} \theta+\cos ^{2} \theta \). (4.) If \( 3 \tan \theta-2=0 \) and \( \theta \in\left[90^{\circ} ; 360^{\circ}\right] \), determine, the value of \( \sqrt{13}(\sin \theta-\cos \theta \) (5.) If \( \cos 52^{\circ}=k \) as illustrated in the diagram, determine each of the following i
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy